The Role Of Interpretation In The Process Of Understanding And Analyzing A Literary Work (Journal of Pedagogical Inventions and Practices, 2026)
This article highlights the role and significance of interpretation in the process of teaching and analyzing a literary work. A deep understanding of a literary text, including its conceptual content and ideological-spiritual essence, is considered an important factor in shaping students’ thinking. The article recommends effective methods such as narration, working with keywords, and the spiral method in teaching literary texts. The process of understanding a literary work is evaluated as an essential stage in developing students’ aesthetic taste, vocabulary, and thinking skills